Guidance on the Conduct of Clinical Research within OECD Countries during the Early Stages of the COVID-19 Pandemic: A Systematic Review - Renu Bhutkar; Jack C. Collins; Claire L. O'Reilly; Sarira El-Den (MDPI AG, 2023)
Background: In response to the COVID-19 pandemic, member countries of the Organisation for Economic Co-operation and Development (OECD) rapidly published guidance regarding the conduct of clinical research. A systematic review was conducted to explore the recommendations issued in relation to the commencement, continuation and termination of clinical research during the early phases of the pandemic. Methods: Searches consisting of the terms "COVID-19", "clinical research", and "guidance", were conducted in PubMed, Embase, MEDLINE, Trip, Guidelines International Network, and Google in April-May 2021 (up to 4 May 2021). Data were extracted from guidance published from OECD member countries and mapped to inductively-developed categories. Results: 9419 references were systematically screened, resulting in the inclusion of 46 publications from 27 OECD countries. Thirty-three sources made recommendations regarding monitoring, risk-benefit assessments and information technology. There was limited specific recommendations made in relation to personal protective equipment (PPE) in the included guidance. Findings demonstrate that guidance differed by publication date demonstrating the rapidly evolving environment within which research was conducted. Importantly, many organisations opted to endorse existing guidance published by the United States' Food and Drug Administration and the European Medicines Agency rather than develop their own recommendations. Conclusions: Given the rapidly evolving nature of the pandemic, particularly in the early stages, findings demonstrate the global response in relation to clinical research conduct, thereby providing important insights for future public health emergencies.